MENINGKATKAN KEMAMPUAN BERHITUNG ANAK MELALUI PERMAINAN BALOK CRUISSENERE PADA ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK AISYIYAH KAMPAR III DESA KAMPAR KECAMATAN KAMPAR TIMUR KABUPATEN KAMPAR - Hulandari, Netti; Isjoni, Isjoni; Solfiah, Yeni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase numeracy skills in children aged 5-6 years through the game cruissenere beam at Kindergarten Aisyiyah Kampar Iii Kampar Village District East Kampar Regency Of Kampar. This study is the kind of research that uses classroom action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. The subjects were children aged 5-6 years were 10 children in kindergarten Aisyiyah. The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. The results showed that the beam cruissenere game can improve numeracy skills in children aged 5-6 years. It can be seen from the increase in the average percentage of numeracy beginning in the first cycle of 54.79% which is the criterion begins to develop (MB) and an increase of 45.17% in the second cycle into 79.56 which are in developing criteria expectations (BSH). So, the game cruissenere beams can improve numeracy skills of children aged 5-6 years in kindergarten Al Mulk Sphere Singkuang Kampar District Kampar regency.Keywords: Ability Numeracy, Tile Games Cruissenere